2012
DOI: 10.3989/mc.2012.63610
|View full text |Cite
|
Sign up to set email alerts
|

Interacción entre cementos de diferente composición y aditivos superplastificantes

Abstract: RESUMENSe ha estudiado el efecto fluidificante (hasta 90 minutos) ejercido por la incorporación de entre 0-1% de aditivos policondensados y policarboxilatos en pastas de cemento Portland, puzolánico, resistente a sulfatos y con adición de caliza.Con la incorporación de los aditivos policondensados, se produjo un incremento de la fluidez de los cementos Portland y puzolánico a mayores dosificaciones que las necesarias en los cementos resistente a sulfatos y con adición de caliza. Éste último presentó la mejor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The average pH-value of the slurries was around 12.5 and insured the alkalinity of the blends made of CEM I, limestone, and clays. In accordance with the literature [8,9], limestone enhances the flowability of CEM I. The present results show an increased flowability of CEM I by ~ 7% in presence of 30% limestone (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…The average pH-value of the slurries was around 12.5 and insured the alkalinity of the blends made of CEM I, limestone, and clays. In accordance with the literature [8,9], limestone enhances the flowability of CEM I. The present results show an increased flowability of CEM I by ~ 7% in presence of 30% limestone (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…For PNS, its spectrum shows that the polymer molecule contains the aromatic C-H stretching band at ca. 3060 cm -1 and aromatic rings modes at 1624 cm -1 and 1595 cm -1 [22,23]. Bands at 1177 and 1030 cm -1 were assigned to sulfonate groups.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is also possible to detect the characteristic XRD peaks of non-hydrated calcium silicates (L, H) and it is observed that the intensity decreases with the curing time. Meanwhile, the intensity of the peak that characterizes the CSH superimposed on that of CaCO3, calcium carbonate (Calcite, (Chen, 2013;Ghorab et al, 2012;Habbaba et al, 2013). The bands observed between 955-947 cm −1 are associated with the type of CH 3 bending vibration, of the methyl functional group adjacent to a carbon atom, and at 849-835 cm −1 to the bending of CH 3 , the methyl group adjacent to an oxygen atom.…”
Section: Hydration Process Of Modified Cement Pastes (X-ray Diffraction)mentioning
confidence: 99%